Neotectonic activity and paleoseismological analysis in Eastern of Antioquia, in the vicinity of Medellin city - Colombia. (2015)
The aim of this investigation was the paleoseismological characterization of eastern Antioquia, using trenches analysis and detailed study of indicators of neotectonic activity, some of which had been reported in previous seismic hazard assessment studies of the Aburra Valley. Through techniques of neotectonic, paleoseismology and also age correlation of Quaternary deposits obtained by several authors, it was found at Alcaravanes site (Marinilla Town), evidences of three seismic events with magnitudes Mw 6.4, 6.6 and 6.5 which displaced recent deposits with maximum ages of 440,000, 37,000 and 8,000 years respectively. Likewise, two prehistoric earthquakes, both with magnitude Mw 6.5 were recognized at the Hamburgo site (Guarne Town), dated between 880,000 and 37,000 years respectively, which proves the existence and activity of La Mosca fault. Finally, the Manantiales site (Rionegro Town) revealed a couple of seismic events with magnitude Mw 6.7 and 6.6 that displaced alluvial terraces in Rio Negro basin with a maximum age of onset of neotectonic deformation of 880,000 years. Latest neotectonic findings change the perspective of seismic hazard in Medellin city and surroundings. Prehistoric earthquakes have occurred in the last million years and created small surface rupture and faulting not related with active mountain fronts. Furthermore, the evidence shows obliterated active faults and efficiency of erosion factors in modeling relief and alluvial fill in the basins of Rionegro Erosion Surface.